Constantine. Volume 3, The voice in the fire - Fawkes, Ray (New 52., 2015)
"Lost and confused in the face of the fallout from his actions in "Forever Evil: Blight," John Constantine has sold himself out to the Cold Flame and is vulnerable to attack by Spellbinder! How will DCU's con man deal with the reprecussions of this universe changing event? Written by Eisner Award nominee Ray Fawkes, John Constantine continues his reemergence as DC Comics' most infamous magician!